2020
DOI: 10.1002/ente.202000165
|View full text |Cite
|
Sign up to set email alerts
|

MoOx‐Doped Ordered Mesoporous Ni/Al2O3 Catalyst for CO Methanation

Abstract: To address the problems of sintering of Ni particles and poor low‐temperature activity of Ni‐based catalysts for CO methanation, MoOx‐doped (x < 3) ordered mesoporous Ni/Al2O3 catalysts are prepared by two different methods, including the impregnation method and evaporation‐induced self‐assembly (EISA) method. The samples before and after the catalytic reaction are thoroughly characterized by scanning electron microscopy and transmission electron microscopy. The ordered mesoporous structure is retained in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…However, it was well found that the surface of CdO shows electron accumulation. , On the other hand, the 3d electron of Ni atoms orbital possesses a vacancy of 0.6 electrons, which is susceptible to receiving electrons from Cd species. This interaction favors the creation of alloy between Ni and Cd as well as alloying and/or chemical interaction with the support is one of the main reasons for binding energy alterations . Therefore, we speculated that the formation of Cd–Ni alloy resulted in the shifting of binding energies in Cd(5%)/Ni(15%)@Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was well found that the surface of CdO shows electron accumulation. , On the other hand, the 3d electron of Ni atoms orbital possesses a vacancy of 0.6 electrons, which is susceptible to receiving electrons from Cd species. This interaction favors the creation of alloy between Ni and Cd as well as alloying and/or chemical interaction with the support is one of the main reasons for binding energy alterations . Therefore, we speculated that the formation of Cd–Ni alloy resulted in the shifting of binding energies in Cd(5%)/Ni(15%)@Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…This interaction favors the creation of alloy between Ni and Cd as well as alloying and/or chemical interaction with the support is one of the main reasons for binding energy alterations. 67 Therefore, we speculated that the formation of Cd−Ni alloy resulted in the shifting of binding energies in Cd(5%)/Ni(15%)@Al 2 O 3 .…”
Section: Activity Testsmentioning
confidence: 99%
“…Synthetic/substitute natural gas (SNG) can be produced from biomass [2], coal gasification to syngas (i.e., a mixture of carbon monoxide (CO) and hydrogen (H 2 )) [3], coke oven gas [4], as well as carbon dioxide (CO 2 ) and carbon monoxide (CO) methanation [1,5]. The latter process is a key step in the production of natural gas, and it can be carried out over noble metals (e.g., palladium (Pd), iridium (Ir), platinum (Pt), and ruthenium (Ru)) [6][7][8] and base metals (e.g., nickel (Ni), iron (Fe), cobalt (Co), and molybdenum (Mo)) [6,7,9,10]. Due to the economic infeasibility of an industrial application of noble metal-based catalysts in the CO methanation process, extensive research is focused on the use of Ni-based catalysts due to their high activity, selectivity, and affordability [1,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The recorded nitrogen adsorption and desorption isotherms for the alumina shows a significant hysteresis at relative pressures P/P 0 above 0.40. These isotherms were type IV, indicating mesoporosity, [13,14] good pore connectivity and the presence of pores with narrow mouths (ink-bottle pores). The structural properties of mesoporous alumina (MA) are presented in Table 2.…”
mentioning
confidence: 99%
“…γ-Al 2 O 3 having higher specific surface area shows high activity in many catalytic application reactions and adsorption application. [6,7] There are many methods are available to prepare mesoporous alumina such as sol-gel method, [8,9] hydrothermal method, [10,11] evaporation-induced self-assembly (EISA) method [12][13][14] and nanocasting method. [15,16] These reported methods were mostly based on using sacrificial anionic, cationic, or non-ionic templates as a structural directing agent to prepare mesoporous alumina.…”
mentioning
confidence: 99%